Stable n-type doping of graphene via high-molecular-weight ethylene amines. Issue 44 (23rd October 2015) - Jo, Insu; Kim, Youngsoo; Moon, Joonhee; Park, Subeom; Moon, Jin San; Park, Won Bae; Lee, Jeong Soo; Hong, Byung Hee
Abstract : We demonstrate a stable and strong n-type doping method to tune the electrical properties of graphene via vapor phase chemical doping with various high-molecular-weight ethylene amines. Abstract : We demonstrate a stable and strong n-type doping method to tune the electrical properties of graphene via vapor phase chemical doping with various high-molecular-weight ethylene amines. The resulting carrier concentration after doping with pentaethylenehexamine (PEHA) is as high as −1.01 × 10 13 cm −2, which reduces the sheet resistance of graphene by up to ∼400% compared to pristine graphene. Our study suggests that the branched structure of the dopant molecules is another important factor that determines the actual doping degree of graphene.